A Brief Overview on Malignancy Risk Index in Pelvic Mass Differentiation - Fainbaum, Nadejda; Batista, Claudio Sergio (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
In this chapter, MRI and its componentes are reviewed. We understand that simplicity of Malignancy Risk Index calculation allows providing, with good accuracy, aid in differential preoperative diagnosis between benign and malignant tumors. Ovarian cancer is seen as the most aggressive gynecological tumor. The morbidity of ovarian cancer is second to cervical cancer and endometrial cancer, but the mortality ranks first of gynecological tumors. Ovarian cancer is the sixth leading cause of mortality from cancer in women. Nearly 70% of epithelial ovarian malignancies are discovered at an advanced stage, when the 5-year survival rate is around 25%. The malignancy risk index (MRI) of ovarian tumors associates menopausal status, ultrasound characteristics and CA-125 serum levels, and has the goal of improving the preoperative distinction between benign and malignant ovarian tumors So, we approuch this tool to regard how we should be find the best way to treat women with pelvic mass.